The Aristotelian Philosophy of the Martial Arts - Hackney, Charles H. (Revista de Artes Marciales Asiáticas, 2012)
Aristotle’s approach to ethics is proposed as a useful way to understand the role that the martial arts play in the life of the martial artist. Neo-Aristotelian philosopher Alasdair MacIntyre, in his classic work After Virtue, introduces the concept of a eudaimonic practice, a form of social activity in which pursuing excellence in the practice results in the practitioner also becoming a better person. It is argued that the martial arts can best be described as such a practice. This approach reconciles a broad range of divergent perspectives on the martial arts, and coherently describes how training as a martial artist can contribute to high levels of functioning in one’s relationships and social roles, connecting the martial arts to the overall process of becoming a morally-excellent human being through growth in the virtues.